Dimeric and dipolar ground state orders in colloidal molecular crystals - Trizac,Emmanuel (2010)
A two dimensional colloidal suspension subject to a periodic substrate evolves into a colloidal molecular crystal under situationsofstrongconfinement. Wefocusonthelongrangeorientationalordertherebyemerging, inthegroundstate. We study by simulations the situations where in each trap lies a pair of identical colloids, or alternatively a pair of oppositelychargedmacroions. We consider square or triangular geometries for the periodic confinement, together with less symmetric distorted lattices.